A Study of the Effectiveness of Flipped Classroom of Teaching in Blended Learning - Sam, Man Keong; Ng, Geok Ling (2016)
Blended courses (also known as hybrid or mixed-mode courses) are classes where a portion of the traditional face-to-face instruction is replaced by web-based online learning. Blended courses have claimed to be the most popular choices for students at some overseas institutions where they are offered. At first glance, this popularity seems intuitive because blended courses allow students and faculty to take advantage of much of the flexibility and convenience of an online course while retaining the benefits of the face-to-face classroom experience. However, many local institutions appear to be struggling with conceptualising and implementing blended learning.The present study aims to investigate the effectiveness of Flipped Classroom of teaching in blended learning.Feedback survey of two groups of students (Age : 18 – 20 years) studying CAD module at Singapore Polytechnic was carried out: one group studied using the mixed mode (Conventional + Flipped during the 3rd term); another group studied using the pure mode (Flipped from the beginning). Students are asked to rate flipped classroom : Q1(a) in using the in-class time to help them to learn in class/to do homework or tutorial in class; Q1(b) in shaping them to be a more independent and responsible learner.The main findings from t –test for two independent samples are:(a) For Question 1(a) : There is no difference between the two modes (at α = 0.05), i.e. flipped classroom did not help students learning in the classroom as compared to traditional ‘face-to-face teaching'. In other words, both modes are suitable or effective for teaching CAD module;(b) For Question 1(b) : There is a significant difference between the two modes(at α = 0.05), i.e. Pure Mode is effective in shaping students to be more independent and responsible learner. In other words flipped classroom is an effective model to be adopted in blended learning for training students to be more independent and responsible.